2021
DOI: 10.1200/op.21.00144
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Cancer Care During the COVID-19 Pandemic in Alberta: Evidence From a Mixed Methods Evaluation and Key Learnings

Abstract: PURPOSE This study reports on a mixed methods evaluation conducted within a provincial cancer program in Alberta, Canada. The purpose was to capture key learnings from a rapid virtual care implementation because of the COVID-19 pandemic and to understand the impact on patient and staff experiences. METHODS Administrative data were collected for 21,362 patients who had at least one virtual or in-person visit to any provincial cancer center from April 1, 2020, to June 10, 2020. Patient surveys were conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 15 publications
2
39
0
Order By: Relevance
“…Many in-person interactions were transitioned to telehealth, which is the provision of health care remotely by means of telecommunications technology (e.g., telephone, video) [ 7 , 8 ]. Increases in telehealth visits were observed across Canada at the start of the pandemic [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many in-person interactions were transitioned to telehealth, which is the provision of health care remotely by means of telecommunications technology (e.g., telephone, video) [ 7 , 8 ]. Increases in telehealth visits were observed across Canada at the start of the pandemic [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other Australian studies have found that patients have less confidence in doctors’ ability to monitor health with telehealth [ 10 , 17 , 19 ]. While some international studies have suggested that the lack of physical contact and limited visual cues in telehealth present challenges to health professionals [ 15 , 36 ], other studies suggest that doctors compensate for this in video consultations by increasing their use of and attention to body language [ 36 ]. Australian patients’ concerns regarding the adequacy of their monitoring through telehealth may reflect the use of the telephone and unfamiliarity with these appointment types.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies included in the review were from countries other than Australia and most reported on the experience of using video technology for appointments [ 11 ]. Studies published subsequently have continued to demonstrate high levels of satisfaction with telehealth for outpatient appointments in mixed patient populations, with video [ 12 14 ] and telephone [ 15 ] formats. However, despite high satisfaction, multiple studies have also shown that most patients prefer in-person consultations [ 16 ] suggesting that a more nuanced understanding of telehealth experiences is needed.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to recognize that the error varied week to week, with larger discrepancies between actual and predicted data during the weeks of 26 February 2020 and 4 March 2020. This could be due to the outbreak of COVID-19 in Alberta, which occurred in February 2020 and caused considerable disruptions within cancer care [33,34]. Healthier patients, including those with low symptom complexity, may have been shifted to a virtual appointment and it has been shown that few virtual patients completed the PPF [34].…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the outbreak of COVID-19 in Alberta, which occurred in February 2020 and caused considerable disruptions within cancer care [33,34]. Healthier patients, including those with low symptom complexity, may have been shifted to a virtual appointment and it has been shown that few virtual patients completed the PPF [34]. Therefore, these patients would not have been included in the dataset, resulting in fewer low complexity patients being represented.…”
Section: Discussionmentioning
confidence: 99%